The influence of apparatus competence, leadership style, tri hita karana culture and society participation on the effectiveness of village fund management - Ni Ketut Rasmini; Putu Sri Harta Mimba (Universitas Hayam Wuruk Perbanas, 2021)
This study aims to determine the effect of the apparatus competence, leadership style, Tri Hita Karana culture and society participation on the effectiveness of village fund management. The sample of this study were taken from 100 villages in Tabanan Regency with the number of respondents as many as 300 respondents. The method for determining the sample were the proportionate stratified random sampling and data collection using a questionnaire. Data were analyzed using multiple linear regression analysis. This study shows that the apparatus competence, leadership style, and society participation have a positive effect on the effectiveness of village fund management. Meanwhile the Tri Hita Karana culture not significantly affect the effectiveness of village fund management. This indicate that the better the apparatus competence, leadership style, and society participation, the better the effectiveness of village fund management..